Investigating the Asymmetric Impact of the Stock Market Index on the Real Estate Price Index - Sakineh Sojoodi; Morteza Ashoor; Elmira Azizi Norouzabadi (تحقیقات مالی)
AbstractObjectiveThe dynamic relationship between stock prices and housing prices has been an important topic of discussion in the academic and professional literature. The impact of stock prices on housing prices can be examined through two substitution effects and the wealth effect. Real estate and stocks are both assets and can also be considered investment options. The connection between these two assets, housing and stocks, can be interpreted as a substitution effect. This implies that a high return on investment in the stock market may lead investors to divest from the housing market, resulting in a decrease in demand and housing prices. In this case, stock prices will harm housing prices. When housing is considered as a consumer good, the effect of wealth is more pronounced. An increase in income and wealth, including financial assets due to the increase in stock prices, has a positive effect on the total consumption expenditure, including housing costs. More specifically, because homeowners receive windfalls from stocks, the wealth effect of these windfalls increases the purchase of houses as a consumer good. In other words, the wealth effect establishes a positive correlation between stock prices and housing. This is because high returns in the stock market augment the overall wealth of homeowners, enhancing their capacity to invest in additional real estate. Therefore, the stock market index can have a positive or negative effect on housing prices. It is necessary to examine this relationship for each country in detail and based on statistical evidence. Accordingly, in the present study, the effect of the stock market index on housing prices in Iran is investigated. MethodsTo reach the research goals, data spanning from 1971 to 2020 is utilized. To test the research hypotheses, the NARDL method was used to identify possible asymmetries effect of positive and negative shocks of the stock price index on the housing price index. ResultsFindings show that in the short run, positive and negative shocks in the stock market index have no significant effect on the housing price index, but in the long term, positive shocks in the stock market index have a positive effect on the housing price index, while the effect of negative shocks on the housing price index is insignificant. ConclusionAccording to the obtained results, due to the substantial impact of stock market fluctuations on housing prices in Iran, it is recommended that policymakers take the following into account when formulating stock market policies. First, in the policymaking process for the housing sector, where the anticipation of housing price trends is crucial, careful attention should be given to potential shifts in the stock market index. Next, a long-term boom in the stock market correlates with an increase in housing prices, while the impact of a stock market downturn on housing price increases is deemed insignificant. Consequently, policies promoting a stock market boom can be considered as a contributing factor to the rise in housing prices.